Zoo professionals and volunteers in the U.S: experiences and prevalence of burnout, mental health, and animal loss - McDonald, Shelby E.; Kogan, Lori R.; Nageotte, Nichole L.; Currin-McCulloch, Jennifer; Dickler-Mann, Rachel (Frontiers in Psychiatry, 2024)
Introduction: Burnout and mental health among animal care and health professionals (ACHPs) has received increasing attention in recent years. Despite rapid growth of research in this area, the wellbeing of individuals who work and/or volunteer in zoo settings has received minimal attention.Method: An anonymous online survey was created to evaluate zoo staff and volunteers' experiences of animal-related loss, rates of professional fulfillment and burnout, mental health, perceived organizational support, and resilience. Participants included 1695 zoo professionals (72% ACHPs, 20% other staff) and volunteers (7%) who were recruited through relevant professional listservs and online platforms, and flyers on zoo grounds.Results: ACHPs reported higher levels of anxiety, depression, and burnout and lower levels of professional fulfillment than other zoo staff and volunteers. The most common animal-related losses experienced by ACHPs in the past year were unexpected death (80%) and anticipated loss (74%), with more than half of these losses occurring within the past 3 months. ACHPs' reported bond with animals under their care was positively associated with depression and anxiety. Having a formal ritual or process following the death of an animal was positively associated with job fulfillment and perceived organizational support and negatively associated with depression and burnout-yet only 17% of participants in our sample indicated that their zoo had such a process or ritual. Discussion: Our findings suggest that many ACHPs are struggling with burnout, anxiety, depression, and low rates of professional fulfilment and perceived organizational support. We recommend that zoos develop organizational plans that foster a culture which normalizes and validates grief/loss experiences and is proactive in responding to animal loss, related trauma, and other occupational stressors. The results of this research demonstrate the need for systemic changes within the zoo industry, for the betterment and welfare of both humans and the animals under their care.